Effectiveness of Using Story Maps in Improving Students’ Reading Comprehension of Narrative Text - Rachma, Nadia Elva; Dari, Retno Wulan (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study investigated the effectiveness of story mps in improving students’ reading comprehension of narrrative texts at the vocational high school level. Many vocational students encounter difficulties in understanding narrative texts, particularly in identifying story elements such as characters, setting, plot, and resolution. Story maps were implemented as a visual learning strategy to assist students in organizing narrative information systematically. This research employed a quantitative approach using a quasi-experimental design. The participants consisted of two classes on eleventh-grade on vocational high school, divided into an experimental group and a control group. The experimental group received instruction using story maps, while the control group was taught using conventional reading methods. Data were collected through reading comehension tests administered as pre-test and post-test. The data were analyzed using normality testing, homogeneity testing, the Mann-Whitney U test, and effect size analysis. The result revealed that there weas no statistically significant difference between the experimental and control groups (p=0.279 > 0.05). However, the experimental group achieved a higher mean score than the control group, indicating a positive effect of story maps on students’ reading comprehension. Although the effect was not statistically significant, the findings suggest that story maps can be an effective instructional strategy to support students’ understanding of narrative texts. Therefore, integrating story maps with other reading strategies is recommended to enhance reading comprehension in vocational school contexts.